Күн белсенділігі мен ғарыштық сәулеленудің Жердің жаһандық климатына әсері - Naurzbaeva, A.Zh.; Alimgazinova, N.Zh.; Manapbayeva, A.B.; Ikramova, S.B. (Хабаршы. Физика сериясы, 2018)
At present a large body of evidence indicates that solar activity and galactic cosmic rays variability has a significant impact on different processes in Earth’s atmosphere such as global climate formation and the ozone layer thickness variation. However, due to the complex dynamics of solar activity, cosmic rays flux and global temperature widely divergent conclusions on the link between these quantities can be made, from arguing for the direct correlation between solar activity and global temperature to totally denying it or claiming inverse correlation.In recent the so-called convergent cross-mapping technique has been developed on the basis of Packard-Takens theorem which makes it possible to investigate the cause and effect relationship between time series of two quantities even when it has not been established using conventional procedures. This method has been applied by a number of researchers to the analysis of correlations between various chaotic processes. In this paper the results of applying of this technique to analysis of correlations between solar activity and global temperature are presented. This new method shows that solar activity and cosmic rays have a noticeable effect on the global temperature: the global temperature anomalies values estimated on the basis of attractors, represented by time series of cosmic rays and solar activity, have a high correlation with its measured values.